True or false :
Let Q be a positive integer with all 3 n identical digits, that is Q = 3 n digits a a a a a a a … a . Then, 3 n divides Q for positive integers n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
As pointed out in the comments, this solution hasn't provided the induction prove that " 1 1 1 . . . 1 3 n is divisible by 3 n , which is the crux of the problem.
This gap is easily filled by observing that 1 1 1 . . . 1 3 n = 1 1 1 . . . 1 3 n − 1 × 1 0 … 0 1 0 … 1 where the first term is a multiple of 3 n − 1 and the second term is a multiple of 3.
In fact, we can show that 3 n is the highest power of 3 that divides 1 1 1 . . . 1 3 n form the above observation.
Do note that even though the statement "if sum of the digits of a number is 3 or multiple of 3, this number is divisible by 3" is true, it doesn't follow by induction that "if sum of the digits of a number is 3 n or a multiple of 3 n , this number is divisible by 3 n ". This is true only for n = 1 , 2 . A simple counterexample for n = 3 is 9 9 8 1 and for n ≥ 3 , we can construct the counterexample 2 7 2 7 … 2 7 4 5 where 2 7 is repeated as many times so that the sum of digits is 3 n . This number is not divisible by 2 7 = 3 3 and hence not divisible by 3 n ∀ n ≥ 3 .
However, the statement 3 n ∣ 3 n times 1 1 1 … 1 1 is true ∀ n ≥ 1 and can be proved by induction. Here 's a nice inductive proof of this statement.
Q = ( 9 a ) ( 1 0 ( 3 n ) − 1 ) 3 n ∣ Q ⟹ 3 n ∣ ( 9 a ) ( 1 0 ( 3 n ) − 1 ) ⟹ 3 n + 2 ∣ a ( 1 0 ( 3 n ) − 1 )
So the problem is equivalent to proving 3 n + 2 ∣ ( 1 0 ( 3 n ) − 1 ) . This can be done by induction.
It is easy to test the statement is true for n = 1 . Assume the statement is true for n = k so 3 k + 2 ∣ ( 1 0 ( 3 k ) − 1 ) :
1 0 ( 3 k + 1 ) − 1 = 1 0 3 ( 3 k ) − 1 = ( 1 0 ( 3 k ) ) 3 − 1 = ( 1 0 ( 3 k ) − 1 ) ( ( 1 0 ( 3 k ) ) 2 + 1 0 ( 3 k ) + 1 ) ( ( 1 0 ( 3 k ) ) 2 + 1 0 ( 3 k ) + 1 ) ≡ ( ( 1 ( 3 k ) ) 2 + 1 ( 3 k ) + 1 ) ≡ 1 + 1 + 1 ≡ 0 ( m o d 3 )
Combining this and the inductive hypothesis gives:
3 ( 3 k + 2 ) ∣ 1 0 ( 3 k + 1 ) − 1 ⟹ 3 ( k + 1 ) + 2 ∣ 1 0 ( 3 k + 1 ) − 1
So it is proved by induction that 3 n + 2 ∣ ( 1 0 ( 3 n ) − 1 ) for all positive n making the statement:
True
Great approach, using the hints in the question statement to guide the solution.
Problem Loading...
Note Loading...
Set Loading...
Given that Q = 3 n a a a . . . a we can write that Q = a × 1 0 3 n + a × 1 0 3 n − 1 + . . . + a × 1 0 0 = a ∑ J = 1 3 n 1 0 J = a [ 1 0 − 1 1 0 3 n − 1 ] = a [ 9 9 9 9 . . . 9 3 n ] = a ⎣ ⎡ 1 1 1 . . . 1 3 n ⎦ ⎤ . The criterion of divisibility of 3 says that the: "if sum of the digits of a number is 3 or multiply of 3, this number is divisible by 3". Then, for induction we can proof that the number 1 1 1 . . . 1 3 n is ever divisible by 3 n Therefore 3 n divides to Q for all n integer positive